Revisiting Obedience. In the Face of Abuses of Power in Consecrated Life - Martínez-Gayol Fernández, ACI, Nurya (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2024)
Within the framework of research on abuses of power in the ecclesial context, this article focuses on the question of obedience and tries to clarify whether this vow, within consecrated life, is a factor that facilitates such abuses. To this end, the definitions of theological and religious obedience are clarified, theological foundations are given, and consequences are drawn for a full experience of the authority-obedience relationship among consecrated persons.
Keywords: abuse; power-authority; theological obedience; religious obedience; social obedience